Taxonomic and morphological survey of the Lygephila lusoria (Linnaeus, 1758) species-group with description of a new species (Lepidoptera, Erebidae, Toxocampinae) - Oleg Pekarsky (ZooKeys, 2013)
The taxa of the Lygephila lusoria (Linnaeus, 1758) species-group are revised. The genital features of all known taxa are described and illustrated with special reference to the structure of vesica. The male genitalia of L. pallida pallida (Bang-Haas, 1907) are described and illustrated for the first time. L. pallida subpicata (Wiltshire, 1971) is treated here as a species, L. pallida subpicata (Wiltshire, 1971), stat. n., distinct from L. pallida. A new species, L. minima, sp. n., from South Russia is described. Illustrations of the holotype and its genitalia are provided; a diagnostic comparison with L. pallida is given. L. alaica Remm, 1983 is included in the L. lusoria species-group for the first time.